Community Empowerment of MSME Owners by the Office of Micro, Small and MSME Cooperatives in Palembang City - Muhammad Punggawa Kandis; Sriati Sriati; Rudy Kurniawan (Journal La Bisecoman, 2024)
Empowering Micro, Small, and Medium Enterprises (MSMEs) in Palembang City is a priority in overcoming the challenges faced by local businesses. Although the number of UMKM is increasing, there are still problems such as a lack of understanding in managing the business and constraints in marketing, especially through social media. The Palembang City Office of Cooperatives, UMKM and Industry is responsible for empowering the community of UMKM owners through mentoring, training and access to technology. This research uses a qualitative method with a focus on UMKM development strategies. Data were obtained through observation, interviews, and documentation. Empowerment is carried out through the stages of awareness, capacity building, and empowerment. The results showed an increase in knowledge and skills of UMKM actors as well as improved product quality and marketing. The community empowerment approach through the Palembang City Cooperative and MSME Office has a positive impact on the development of MSMEs and the economy of Palembang City.